(12b+7)(5b-15)=0

Simple and best practice solution for (12b+7)(5b-15)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (12b+7)(5b-15)=0 equation:


Simplifying
(12b + 7)(5b + -15) = 0

Reorder the terms:
(7 + 12b)(5b + -15) = 0

Reorder the terms:
(7 + 12b)(-15 + 5b) = 0

Multiply (7 + 12b) * (-15 + 5b)
(7(-15 + 5b) + 12b * (-15 + 5b)) = 0
((-15 * 7 + 5b * 7) + 12b * (-15 + 5b)) = 0
((-105 + 35b) + 12b * (-15 + 5b)) = 0
(-105 + 35b + (-15 * 12b + 5b * 12b)) = 0
(-105 + 35b + (-180b + 60b2)) = 0

Combine like terms: 35b + -180b = -145b
(-105 + -145b + 60b2) = 0

Solving
-105 + -145b + 60b2 = 0

Solving for variable 'b'.

Factor out the Greatest Common Factor (GCF), '5'.
5(-21 + -29b + 12b2) = 0

Factor a trinomial.
5((-7 + -12b)(3 + -1b)) = 0

Ignore the factor 5.

Subproblem 1

Set the factor '(-7 + -12b)' equal to zero and attempt to solve: Simplifying -7 + -12b = 0 Solving -7 + -12b = 0 Move all terms containing b to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + -12b = 0 + 7 Combine like terms: -7 + 7 = 0 0 + -12b = 0 + 7 -12b = 0 + 7 Combine like terms: 0 + 7 = 7 -12b = 7 Divide each side by '-12'. b = -0.5833333333 Simplifying b = -0.5833333333

Subproblem 2

Set the factor '(3 + -1b)' equal to zero and attempt to solve: Simplifying 3 + -1b = 0 Solving 3 + -1b = 0 Move all terms containing b to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1b = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1b = 0 + -3 -1b = 0 + -3 Combine like terms: 0 + -3 = -3 -1b = -3 Divide each side by '-1'. b = 3 Simplifying b = 3

Solution

b = {-0.5833333333, 3}

See similar equations:

| Cos(x)+sen(x)=0 | | x+x+24+2(x+24)=376 | | 4(d-7)=2(3x)+6 | | N+4=(3)-n | | x-14=194 | | -11+10(3)=2c | | -7.8+4.8=7x-8.9-6x | | -11+10r=2c | | 4(6+3)+2(1+2)= | | a/b=7/18 | | 9.5+0.25x=9.5 | | (3x/3)^2x | | 935+0.25x=9.5 | | -14x+70= | | X-39+x+6=180 | | x-a=m | | x+24+3x-17-3x-22= | | x+10-y=4198 | | W/25-790=1400 | | 4b(6-7b)=2c | | 3(-1+5x)=-18 | | 4d-1=d+8 | | 10x^4-63x^3+52x^2+63x+10=0 | | 6y^2+12y-30=0 | | -6(x-5)-6=24 | | 4(x-1/2)9 | | (11+x)(16+x)=500 | | 2y-5+3y-7= | | x+3(y)+2(z)=88 | | 2/5x-2=8-13/5x | | x+3x+2x=88 | | x*x=x*x-8 |

Equations solver categories